2022
DOI: 10.3390/ijerph19137748
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Infection on Cognitive Function and the Implication for Rehabilitation: A Systematic Review and Meta-Analysis

Abstract: There is mounting evidence that patients with severe COVID-19 disease may have symptoms that continue beyond the acute phase, extending into the early chronic phase. This prolonged COVID-19 pathology is often referred to as ‘Long COVID’. Simultaneously, case investigations have shown that COVID-19 individuals might have a variety of neurological problems. The accurate and accessible assessment of cognitive function in patients post-COVID-19 infection is thus of increasingly high importance for both public and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 104 publications
(143 reference statements)
2
26
0
1
Order By: Relevance
“…Our findings in this review are consistent with findings of other investigators, who reported symptoms affecting physical and mental health. They reported post COVID-19 psychological and neuropsychological concerns (anxiety and depression, PTSD, sleep and cognition deficits), even in people who had never had a mental health condition, which is similar to our findings [ 49 , 50 ]. In another study conducted by Van Kessel et al, it was found that psychological, cognitive and social symptoms were associated more with post-acute COVID-19 syndrome and less with long COVID-19 haulers.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings in this review are consistent with findings of other investigators, who reported symptoms affecting physical and mental health. They reported post COVID-19 psychological and neuropsychological concerns (anxiety and depression, PTSD, sleep and cognition deficits), even in people who had never had a mental health condition, which is similar to our findings [ 49 , 50 ]. In another study conducted by Van Kessel et al, it was found that psychological, cognitive and social symptoms were associated more with post-acute COVID-19 syndrome and less with long COVID-19 haulers.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguing, hospitalization did not have a significant effect on test performance, and there was no statistical difference between NH patients, those who required hospitalization with or without oxygen and those that received ICU care. These results are consistent with previous reports of cognitive and neurological sequels 4 months after COVID‐19 infection (Mattioli et al., 2022 ) and where cognitive decline was independent of disease severity (Hadad et al., 2022 ; Houben & Bonnechère., 2022 ). Other studies also found no differences when considering treatment with mechanical ventilation or oxygen supply (Beaud et al., 2021 ; García‐Sánchez et al., 2022 ; Woo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hadad et al (2022) found that disease severity, premorbid condition, pulmonary function test, and hypoxia did not contribute to cognitive performance. In addition, there is not a clear link between the severity of the infection and the degree of cognitive impairment (Houben & Bonnechère, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Виявлені у даному дослідженні гірші показники когнітивного функціонування в УБД з НПР узгоджуються з даними досліджень, що встановили наявність у комбатантів порушень когнітивного функціонування [26][27][28][29], а також з дослідженнями, які виявили несприятливий вплив COVID-19 на когнітивну сферу [30][31][32][33]…”
Section: особливості психопатологічної симптоматики в учасників бойов...unclassified